NEW INCIDENCE OF LUNG CANCER IN HANOI IN THE PERIOD 2015 - 2019 (Vietnam Journal of Community Medicine, 2022)
Objectives: This study on the epidemiology of lung cancer in Hanoi from 2015 to 2019 offeredcrucial details on the situation of the disease and epidemiological characteristics of lung cancer.Methods: Data was collected retrospectively in a descriptive study with analysis.Results: In Hanoi, 7389 new cases of lung cancer were diagnosed between 2015 and 2019. Inwhich, the age group 70-79 had the highest new incidence rate of age-specific lung cancer (116.2cases/100.000 population).The crude incidence rate was 20.3/100.000; the age-standardizedincidence rate was 19.6/100.000 (with 31.6/100.000 for males and 9.7/100.000 for females); and theage-standardized incidence rate in the inner city was lower (13.7/100.000) than that in the suburbanarea (19.4/100.000).Conclusion: Lung cancer was still a public health issue that required special attention. Effectivetobacco control initiatives, early detection screening, and improved treatment quality were the toppriorities for reducing the negative effects of lung cancer in the community.
Keywords: Incidence rate, lung cancer, Hanoi.